Bioactive Chitosan/β-Tricalcium Phosphate Coatings on Titanium: Experimental Optimization and DFT Insight - Milusheva, R.Yu..; Nurgaliev, I.N.; Abilkasimov, A.B.; Rashidova, S.Sh. (Eurasian Journal of Chemistry, 2025)
The development of bioactive coatings combining biopolymers and calcium phosphate ceramics offers an effective strategy to improve osseointegration and functional performance of titanium-based implants. In this study, highly purified Bombyx mori chitosan (CS-BM) and β-tricalcium phosphate (β-TCP) were used to fabricate hybrid coatings on titanium substrates via electrochemical deposition under optimized conditions (52 °C, pH 6.6–7.0, 2.0–4.0 mA·cm–2). SEM and AFM analyses revealed uniform, strongly adherent twolayer structures with microtopography (1–10 μm roughness) favorable for bone ingrowth, while elemental analysis confirmed complete Ca- and P-rich coverage. Density functional theory (DFT) modeling confirmed the cooperative role of Ca2+ and PO4 3– in bridging CS-BM to TiO2, contributing to coating stability. In vivo studies demonstrated that CS-BM/TCP-coated implants accelerated early contact osteogenesis, dense trabecular bone formation, and stable bone–implant integration compared to uncoated controls. In an experimental osteoporosis model, intramuscular administration of CS-BM with active calcium or calcium–vitamin D3 significantly enhanced fibroblast-to-osteoblast differentiation, stimulated osteoid synthesis, and led to complete restoration of bone microarchitecture within 21 days. These findings highlight CS-BM/TCP coatings as a sustainable, locally sourced, and highly effective platform for orthopedic and dental implant applications, with additional therapeutic potential in osteoporosis management.
Keywords: chitosan; Bombyx mori; DFT modeling; chitosan coating; β-tricalcium phosphate; TiO2(110); electrochemical deposition; implant; osteogenesis